Designing, deploying, and studying internationally networked collaboration: The Trans-Atlantic and Pacific Project (TAPP) model - Arnó, Elisabet; Duin, Ann Hill; Maylath, Bruce; Mousten, Birthe; Palumbo, Giuseppe; Vandepitte, Sonia; Goetz, Greta (Proceedings of the International Conference on Networked Learning, 2018)
Members of today’s diverse and global workforce increasingly perform their work as part of cross-cultural virtual teams (CCVTs). CCVTs are those teams connected via technology and comprised of people in various locations around the globe whose primary objective of virtual collaboration is to launch, develop, and complete its assigned task. In addition to discipline and technical knowledge, today’s working professionals need cross-cultural competence. As the majority of students will be expected to work effectively on CCVTs, it is imperative to include collaborative work on realistic projects as a means to develop language skills, project management skills, application of specialized skills and knowledge, and intercultural competence. Over the past 18 years, the Trans-Atlantic & Pacific Project (TAPP) has connected 29 universities in 16 countries on four continents, linking writing classes to usability testing and translation studies classes in collaborative projects. TAPP’s main aim is to share insights into collaborative writing across borders and cultures, and, in the course of this work, to gain intercultural competence. The network of partners participating in TAPP establishes links between students in different countries so that each learns from the other. In so doing, students become aware of the diversity of the world community in which their documents travel. The purpose of this workshop is to guide attendees in learning how to join TAPP or to design and run collaborative global virtual collaborative projects on their own. Presenters will share research and practice that addresses the structural, relational, interactional, and technological components of TAPP projects, with emphasis on the study of intercultural competence developed as a result of student global virtual collaboration. Participants will design an international collaborative project based on the TAPP model; this will include how to run and gain support for international collaborative projects in a political environment of rising nationalism.